2021
DOI: 10.3389/fimmu.2020.613114
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Hypoxia Regulates Immune Escape/Invasion: Influence on Angiogenesis and Potential Impact of Hypoxic Biomarkers on Cancer Therapies

Abstract: The environmental and metabolic pressures in the tumor microenvironment (TME) play a key role in molding tumor development by impacting the stromal and immune cell fractions, TME composition and activation. Hypoxia triggers a cascade of events that promote tumor growth, enhance resistance to the anti-tumor immune response and instigate tumor angiogenesis. During growth, the developing angiogenesis is pathological and gives rise to a haphazardly shaped and leaky tumor vasculature with abnormal properties. Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(123 citation statements)
references
References 190 publications
0
102
0
Order By: Relevance
“…Further, Saggar et al found that chemotherapy repopulates hypoxic cells that contribute to treatment failure, possibly due to enhanced nutrient availability following clearance of rapidly proliferating cells [90]. The link between normoxia and chemotherapeutic success likely explains the benefits of hyperbaric oxygen therapy (HBOT) in improving their effectiveness [91][92][93]. The excess oxygen molecules provided by HBOT enhances chemotherapy-induced oxidative stress, thereby lowering the therapeutic dose and mitigating side effects [91][92][93].…”
Section: Hypoxia and Drug Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Further, Saggar et al found that chemotherapy repopulates hypoxic cells that contribute to treatment failure, possibly due to enhanced nutrient availability following clearance of rapidly proliferating cells [90]. The link between normoxia and chemotherapeutic success likely explains the benefits of hyperbaric oxygen therapy (HBOT) in improving their effectiveness [91][92][93]. The excess oxygen molecules provided by HBOT enhances chemotherapy-induced oxidative stress, thereby lowering the therapeutic dose and mitigating side effects [91][92][93].…”
Section: Hypoxia and Drug Resistancementioning
confidence: 99%
“…The link between normoxia and chemotherapeutic success likely explains the benefits of hyperbaric oxygen therapy (HBOT) in improving their effectiveness [91][92][93]. The excess oxygen molecules provided by HBOT enhances chemotherapy-induced oxidative stress, thereby lowering the therapeutic dose and mitigating side effects [91][92][93].…”
Section: Hypoxia and Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Studies in cancer patient cohorts have similarly correlated the presence of hypoxia with an immunosuppressed TME in breast cancer, 45 , 46 clear cell renal cell carcinoma, 47 colorectal cancer, 48 hepatocellular carcinoma, 49–51 melanoma, 52 osteosarcoma, 53 neuroblastoma 43 and pancreatic cancer, 41 , 54 among others. 55 These studies used hypoxia gene signatures to determine the hypoxic state and immune fraction or gene set enrichment analysis to highlight the immune microenvironment. In addition, the coupling of an immune score with a hypoxia score in lung adenocarcinoma, 42 pancreatic cancer, 41 and soft tissue sarcoma 38 revealed significantly lower immune activation in tumors with high hypoxia, compared to their low hypoxia counterparts.…”
Section: The Immune Contexture Of Hypoxic Tumors Remains Inconclusivementioning
confidence: 99%
“…Many proangiogenic factors are upregulated in tumor cells and tumor-associated stromal cells, including vascular endothelial growth factor (VEGF), fibroblast growth factor (FGF), and delta ligand-like 4 (Dll4). Hypoxia is a key inducer of tumor angiogenesis and promotes the expression of various proangiogenic factors in the tumor microenvironment ( Abou Khouzam et al, 2020 ). Recently, antiangiogenic drugs have been widely applied to the treatment of multiple solid cancers, and cancer patients have gained tremendous survival benefits from antiangiogenic therapy.…”
Section: Introductionmentioning
confidence: 99%